Pengembangan Sistem Informasi Penerimaan Peserta Didik Baru (PPDB) Jalur Mandiri (Studi Kasus: SMA 1 Negeri Blitar) - Asha Akbar Permana; Satrio Agung Wicaksono; Niken Hendrakusma Wardani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Junior High School 1 Blitar one of many favourite school at Blitar city, that every year always have increased registrant student. It is known that the process of accepting new students that has been running so far requires a lot of resources in its implementation. Then at each stage of the process, the selection and processing of new student data that is not yet fully computerized, causes it to be less efficient. Likewise the problem on the part of the participants, they complained about the queuing system at the time of registration and the data verification process of the participants which took time. From the various problems above, it can be concluded that there is a need to develop an information system that is expected to be able to help the parties involved in the process of accepting new students of SMAN 1 Blitar. In developing an information system, the basic concept of Software Development Cycle (SDLC) is applied. By selecting the waterfall method, the first phase is a needs analysis which produces 13 system features from 23 functional types & 1 non functional as an illustration of the capabilities of the system created. Modeling the results of the analysis using Unfield Modeling Language (UML) modeling such as use case, activitiy, sequence and class diagrams. After the implementation process, the information system test results using the black-box validation method are declared valid. Followed by UAT results that 92.4% of the system can be received from the stakeholder side with a total of 24 answers "agree" on the completed questionnaire.